Desenvolvimento de método de extração-floculação por aplicação de ondas ultrassônicas em óleo lubrificante usado - Souza, Felipe Oliveira (2015)
This paper proposes an innovative process based on the use of ultrasonic waves (US) for the decontamination of used lubricating oils. The proposed system consisted of applying a sound field through a US bath where the contaminated used lube oil, was (OLUC) mixed with solvents, as ethanol, 2- propanol and 1-butanol inside a cylindrical containers in the ratio 1: 3, respectively. Approximately 20.0 L of pool of lubricating oils contaminated coming from medium and small vehicles were collected in dealership representative of the northern region of the Holy Spirit. The best optimized conditions of operate were: 30 °C temperature; 20 minutes and 37 kHz of US frequenc. The incorporation of OLUC solvents was carried out at 60 °C for 5 XVIII min magnetic stirring at 250 rpm. After the extraction and flocculation operations, the recovered oil was subjected to the determination of their physicochemical properties as ANP Ordinance 130/1999. The analysis identified that the oil recovered by the use of US and 1-butanol has the best overall performance (≈ 80.0% w/w) and properties with fewer acidity (0.0141 mg KOH/g), lower viscosity index (97), lower water content (0.07% w/w) and lower ferromagnetic severity index (1.44). By comparing the developed method, other methods extraction by mechanical or magnetic stirring, it was observed that the application of ultrasound increases the process yield of at least 25% (w/w) and reduces total process time of at least 16 hours. The extraction and flocculation promoted by ultrasonic waves and solvents reduces the energy and the time required. In order to reduce environmental impacts and overall process efficiency, the method developed in this study is very promising.